Complications of Percutaneous Renal Biopsy - Bakdash, Kenaz; Schramm, Kristofer M.; Annam, Aparna; Brown, Matthew; Kondo, Kimi; Lindquist, Jonathan D. (Seminars in Interventional Radiology, 2019)
Percutaneous renal biopsy is widely used for diagnosis, prognosis, and management of nephropathies. Complications may arise after renal biopsy, most commonly in the form of bleeding. Efforts should be taken to optimize modifiable risk factors such as hypertension, thrombocytopenia, and coagulopathy prior to the procedure. Unmodifiable risk factors such as poor renal function, gender, and underlying histologic diagnosis may be used to identify high-risk patients. Delayed presentation of bleeding complications is common, and close clinical follow-up is crucial.
Keywords: renal biopsy; hemorrhage; bleeding complication; embolization; interventional radiology